Estudio de Prefactibilidad para Determinar la Viabilidad de la Implementación de una Línea de Concreto Premezclado en la Empresa Alercoge SAC. En la Ciudad de Pucallpa - Méndez Aguirre, Joel Enrique (2017)
The present research aims to determine the viability, at pre-feasibility level, the implementation of a ready-mix concrete line at the company ALERCOGE SAC in Pucallpa city. This study responds to the opportunity to take advantage of the good growth prospects that the construction sector expects to achieve: 5.40% (2018), 5.40% (2019), 5.40% (2020), 5.00% (2021). For that, the research covered the following main activities: Sectorial study, market study of ready-mixed concrete, technical study, legal and environmental study and economic-financial study. ALERCOGE SAC is a construction company, located in Trujillo city, with more than 15 years of experience providing construction services. Its business strategy is oriented to new markets that offer long-term profitability. Therefore, it has as an investment alternative of the creation of a subsidiary company (ALERMIX) for the production and commercialization of ready-mixed concrete in Pucallpa city. The target market for ready-mixed concrete are contractor’s companies that carry out infrastructure projects in Pucallpa city. According to the market study, the project intends to start its operations with a 12% (31,114 m3) share of total demand and achieve 24% (77,272 m3) of total demand in the fifth year of operation. To achieve this, the efforts will be focused on the positioning of the brand, through an integral service (high quality product and additional services). The project will be located at 8th Km of Centenario Avenue (Pucallpa), an estimated installed capacity of 69,888 m3/year for the first two years, and reach a capacity of 139,776 m3/year for the following three years of operation, through the acquisition of additional M & E. The investment required for the project’s start-up is S /. 5,738,861 and the results obtained from the economic and financial evaluation, with a Weighted Average Cost of Capital (WACC) of 13.81% and a Shareholder Opportunity Cost (COK) of 15.83%, are: NPV Economic: S /. 7,976,425 (NPVE> 0), IRR Economic: 46.74% (IRRE> WACC), Payback: 2.91 years, NPV Financial: S/. 7,914,898 (NPVF> 0), Financial IRR: 57.55% (IRRF> COK) and Payback: 2.32 years. Due to the above, the present project is viable at the pre-feasibility level.